AN ANALYSIS ON HOW ARTISTIC DESIGN IS COMPETING IN THE INTERIOR DESIGN SERVICES INDUSTRY AND A PROPOSAL TO IMPROVE ITS PERFORMANCE - Kang, Woon Tian Raymond (2009)
This management project is about evaluating how Artistic Design, a startup interior design company, is competing in the highly competitive interior design services industry and proposing a strategy for improvements in its competitive position. A critical review of the academic literatures is structured around the two prominent approaches towards competitive advantages: (1) Porter’s framework; and (2) Resource-based View approach. The modified SWAT Analysis Model, a proposed framework which focuses on both industry orientation and the firm-specified insights on competitive advantage, is adopted as the evaluation tool for the subject of the management project. The qualitative approach of case study research is used as the research method in this management project and the data are collected via the in-depth open-ended interviews with the owner of Artistic Design; direct observations and personal experiences; and public information from the internet. The results of analyses have shown that Artistic Design is able to rely on the strengths of its resources and capabilities to enhance its differentiation efforts to better compete in the highly competitive industry and to reduce the threat of price pressure from the customers. However, the weaknesses in its brand name and relationship management with subcontractors have limited the benefits that the company can derive from some of the opportunities identified, and at the same time has reduced its ability to overcome certain threats within the industry. A strategy on strengthening these two weak internal resource and capability has also been proposed.